2017
DOI: 10.26417/ejis.v7i2.p66-75
|View full text |Cite
|
Sign up to set email alerts
|

Experienced and Anticipated Discrimination in Persons with Physical Disabilities in Serbia

Abstract: The aim of this study was to explore extensity (regarding various life domains in which it appears) and intensity of experienced and anticipated discrimination of persons with physical disabilities; (2) to investigate how experienced and anticipated discrimination relate to each other; (3) to explore relations between experienced and anticipated discrimination and certain socio demographic variables (gender, marriage, residence, family type, employment and age). The levels of experienced and anticipated stigma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…Answers on the revised DISC 12 were scaled from 0 to 3. Based on our previous study (Milačić‐Vidojević et al ., ), we decided to use two types of scores: ‐ Discrimination extensity measures the spread of discrimination across various domains of life, regardless of its intensity. This score was calculated by counting the number of items for which the participant scored 1 (a little), 2 (moderately) or 3 (a lot) in each subscale.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Answers on the revised DISC 12 were scaled from 0 to 3. Based on our previous study (Milačić‐Vidojević et al ., ), we decided to use two types of scores: ‐ Discrimination extensity measures the spread of discrimination across various domains of life, regardless of its intensity. This score was calculated by counting the number of items for which the participant scored 1 (a little), 2 (moderately) or 3 (a lot) in each subscale.…”
Section: Resultssupporting
confidence: 59%
“…The first canonical function showed that with increased experienced and anticipated discrimination in everyday life and decreased strategies for overcoming stigma, we can expect to see greater social withdrawal and larger stereotype endorsement amongst people with physical disabilities. In our previous study, which employed the same participants as the present one, it has been shown that discrimination was experienced in all life domains (Milačić‐Vidojević et al ., ), suggesting that due to unpleasant experiences in everyday life persons with physical disabilities endorsed social stereotypes and consequentially withdrew from social life experiences. Rüsch, Lieb, Bohus and Corrigan () found that anticipated discrimination and internalized stigma were closely related, triggered by a previous stigma and discrimination experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, it was realized that they also contribute to discrimination that persons with disabilities experience in family life. 27 The study showed that some participants felt neglected by their families and friends because they were afraid to be associated with them in public gatherings. This has a connection with the superstitious Ghanaian culture which associate negative comments with not only persons with LLA but also to their relatives.…”
Section: Discussionmentioning
confidence: 99%